Identificação e manejo de abelhas nativas para a polinização do mirtilo (Vaccinium corymbosum) em ambiente protegido nas condições tropicais do nordeste brasileiro - Farias, Francisco Felipe Monteiro (2024)
The blueberry (Vaccinium corymbosum) is a temperate crop which produces a small fruit rich in natural antioxidants and benefits from bee pollination. Its commercial production is incipient in Brazil, and there is no information on the pollination and fruiting of this crop in the tropical regions of northeastern Brazil. Therefore, the present work aimed to identify native Brazilian bee species that can be used for blueberry pollination under protected cultivation in the tropical conditions of NE Brazil. To this end, the floral biology and pollination requirements of the crop were investigated, as well as the adaptation to the protected environment, foraging behavior and pollination efficiency of the native bees Melipona flavolineata, Scaptotrigona aff. depilis, Plebeia flavocincta, Frieseomelitta sp. and Xylocopa frontalis. The experiment was conducted at Sítio Ouro Azul, Ubajara-CE, between the months of March and September 2023, when 1,000 plants of the Biloxi variety were used. Pollination requirements were assessed through free pollination treatments and exclusion of floral visitors, while the viability of using bees was assessed by adaptation to the protected environment, foraging behavior, and pollination efficiency (set rate, fruit mass (g) and fruit ripening time). The results showed that the biloxi variety is capable of autopollination and is self-fertile to produce fruits but benefits from manual cross-pollination in terms of weight (p<0.05) and shorter fruit maturation time (p<0.05), as well as pollination by bees. Bees S. aff. depilis and Frieseomelitta sp. did not adapt nor were suitable to pollinate blueberries under the conditions studied. Melipona flavolineata visited the flowers, but with one visit it did not demonstrate significant efficiency (p>0.05) in blueberry pollination, presenting the lowest percentage of fruit set (88%) and not differing from free pollination without bees. On the other hand, P. flavocincta and X. frontalis set 96% and 100% flowers and produced heavier fruits (11.64% and 31.74% more mass) and matured (62 and 66 days) significantly (p<0.05) earlier than the free treatment without bees, respectively. However, significantly better results (p<0.05), with a 41.73% increase in fruit mass, were obtained with free pollination when the three bee species were present. It is concluded that the biloxi variety cultivated in a protected environment and under tropical conditions in NE Brazil, despite capable of autopollination, reaches higher fruit set rates, significantly heavier fruits and earlier maturation when pollinated by X. frontalis, and even better by the complementary action of the native bees M. flavolineata, P. flavocincta and X. frontalis. Keywords: protected cultivation; native bees; Blueberry production; Xylocopa frontalis; agricultural pollination; fruit growing in the northeast Brazil.